Jægerkulturer og fænomenet skyld - Luckert, Karl W. (Religionsvidenskabeligt Tidsskrift, 1986)
This article is a slightly edited Danish version of the opening Fulbright address given at the Department of the History of Religions, Aarhus University. The article introduces definitions of religion, guilt, and religious behaviour, and then introduces a means by which the history of religion can be applied to the evolution of humankind and culture in a timeframe of several thousand years. The theme of guilt in the history of religious humanity is then discussed in three subsections. The first subsection concerns guilt, tools and divine predators, the goal of which is to illuminate the two major forms of guilt-and reconciliation bonding in the course of hominid evolution. This is reconstructed on the basis of recent anthropological theories of cultural evolution and the reshaping of the hominid family tree, from suspected similarities at pre-hominid levels of primate behaviour, as well as from extant Stone Age hunter traditions which, to this day, still contain soteriological solutions to problems of long ago. The second subsection concerns guilt, hunting and healing, the goal of which is to fill the scholastic lacuna concerning primitive hunters’ religious practices especially in relation to the entire primitive hunter-gatherer ethos. The bitter fact of the primitive hunter life, that trickery is a hunter’s actual guilt-producing lifestyle, has never dawned on educated connoisseurs of trickster tales. Primitive folks are portrayed, in spite of what they say or do, as though they face their gods with the same indifference as do their learned visitors. Data which I collected on Navajo hunter traditions substantiate the points in this subsection; while, on the one hand, a healing ceremonial can be understood as a delayed conciliatory hunting rite, it can also be seen, on the other hand, in its restorative function, as a reconciliation ceremony or peace treaty that is performed – on account of human guilt – in accordance with divinely ordained protocol. The third subsection concerns modern versus primitive hunting, the goal of which is to bridge the misunderstanding which academic studies reveal by underlining the extreme pre-suppositional differences between the two forms of hunting.